2015
DOI: 10.1177/0165025415576815
|View full text |Cite
|
Sign up to set email alerts
|

Maternal parenting and social, school, and psychological adjustment of migrant children in urban China

Abstract: This study examined the relations of maternal warmth, behavioral control, and encouragement of sociability to social, school, and psychological adjustment in migrant children in China. The participants were 284 rural-to-urban migrant children (M age ¼ 11 years, 149 boys) in migrant children's schools and their mothers. Data on parenting were collected from mothers' reports. Data on children's adjustment were collected from multiple sources including peer assessments, teacher ratings, self-reports, and school r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 66 publications
(94 reference statements)
1
14
0
Order By: Relevance
“…Although child sociability is influenced by various factors such as the sociodemographic variables of gender (Elliott, Barnard, & Gresham, 1989; Russell, Hart, Robinson, & Olsen, 2003), age (Bee & Boyd, 2002), and number of children in the family (Ladd & Hart, 1992), one of the strongest predictors of child outcomes and sociability, in particular, is parental practices. These practices, such as warmth, control, encouragement, and engagement, are based on parental perception of the role of parenting and were found to predict child sociability (Stevenson & Crnic, 2013; Zhou, Eisenberg, Wang, & Reiser, 2004; Zhao, Chen, & Wang, 2015). It is reasonable to assume that there are psychological mechanisms that underlie such parental practices enabling development of child sociability.…”
Section: Children’s Sociabilitymentioning
confidence: 99%
“…Although child sociability is influenced by various factors such as the sociodemographic variables of gender (Elliott, Barnard, & Gresham, 1989; Russell, Hart, Robinson, & Olsen, 2003), age (Bee & Boyd, 2002), and number of children in the family (Ladd & Hart, 1992), one of the strongest predictors of child outcomes and sociability, in particular, is parental practices. These practices, such as warmth, control, encouragement, and engagement, are based on parental perception of the role of parenting and were found to predict child sociability (Stevenson & Crnic, 2013; Zhou, Eisenberg, Wang, & Reiser, 2004; Zhao, Chen, & Wang, 2015). It is reasonable to assume that there are psychological mechanisms that underlie such parental practices enabling development of child sociability.…”
Section: Children’s Sociabilitymentioning
confidence: 99%
“…However, most studies on IMs’ health factors have just focused on a particular aspect of social life, such as economic status or acculturation. [ 15 19 ]. Only a few studies have explored the IMs’ health status from a more comprehensive social perspective including personal and social factors.…”
Section: Introductionmentioning
confidence: 99%
“…By 2007, some studies reported over 300 migrant schools enrolling 170,000 migrant children in Beijing [50] [51]. In 2011, although many migrant schools had been closed down, approximately 140,000 children were still reported as enrolled in migrant children's schools in Beijing [52].…”
Section: Unlicensed and Unregulated Migrant Schools With Low Qualitymentioning
confidence: 99%
“…Their study called for multi-level intervention strategies with respect to individual adjustment, family intervention, community support, school improvement and policy reform. [52] studies the positive role of maternal warmth and encouragement of sociability in migrant children's social and school achievement and psychological adjustment [52]. [75] offers two intervention strategies to improve migrant children's academic performance, to increase their identification with learning and to reduce the threat of stereotypes at school.…”
Section: Psychological Well-beingmentioning
confidence: 99%